The role of inter-professional collaboration to support science learning: An exploratory study of the perceptions and experiences of science teachers, public librarians, and school librarians - Latham, Don; Julien, Heidi; Gross, Melissa; Witte, Shelbie (Library & Information Science Research, 2016)
This cross-disciplinary, cross-institutional exploratory study looks at school librarians', public librarians', and high school science teachers' perceptions of and experiences with inter-professional collaboration to support science learning. The research explores the perceptions and experiences of professional librarians and science teachers regarding 1) inter-professional collaboration, including barriers to collaboration; 2) the relevance of 21st century skills to the teaching of science; and, 3) collaborations that can support and foster the teaching and learning of 21st century skills in the content area of science. Results from focus groups conducted with science teachers, public librarians, and school librarians revealed great potential for, but also significant challenges to, inter-professional collaboration.